Enhancement of antioxidant enzymes activities and growth performance of Zoysia macrostachya Franch. & Sav. subjected to salt heterogeneity (Bangladesh Journal of Botany, 2025)
Clone integration exerts a vital part in ecologically adapting to salinity heterogeneous habit of clonal plant. Nonetheless, little is known about how clonal integration affects the physiology and developmentof Zoysia macrostachya under salinity heterogeneous habit. The present work used clonal fragments from stoloniferous Z. macrostachya that had six consecutive internodes as experimental materials, the daughter ramets were grown in different salinity concentrations solution, while the parent ones were watered under normal condition, stolons were severed or retained intact. As a result, Clonal integration significantly increased the activities of Ascorbate Peroxidase (APX), Glutathione Peroxidase (GPX) and Superoxide Dismutase (SOD), and reduced •O2– production rate, H2O2 and MDA contents and electrolyte leakage of daughter ramets subjected to salinity heterogeneous habit, however, there was no effect on Peroxidase (POD) activity of daughter ramets. Clonal integration benefited clonal fragment and daughter ramets growth, but there was no significant effect on parent ramets growth. which indicated that a physiological integration existed from parent ramets to daughter ramets, and the latter benefited from parent ramets under salinity heterogeneous habit, which was important for Z. macrostachya adaption to salt stress.Bangladesh J. Bot. 54(1): 7-15, 2025 (March)